2023
DOI: 10.1257/aeri.20220006
|View full text |Cite
|
Sign up to set email alerts
|

The Unequal Consequences of Job Loss across Countries

Antoine Bertheau,
Edoardo Maria Acabbi,
Cristina Barceló
et al.

Abstract: We document the consequences of losing a job across countries using a harmonized research design applied to seven matched employer-employee datasets. Workers in Denmark and Sweden experience the lowest earnings declines following job displacement, while workers in Italy, Spain, and Portugal experience losses three times as high. French and Austrian workers face earnings losses somewhere in between. Key to these differences is that southern European workers are less likely to find employment following displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
7
1
1
Order By: Relevance
“…Previous literature has found large lasting negative effects of displacement on earnings (e.g., Jacobson et al, 1993;Davis and Von Wachter, 2011). Using a mass-layoff instrument, Bertheau et al (2023) found that displaced Swedish workers have a 5 percentage point higher probability of being unemployed and 10 percentage points lower earnings than non-displaced workers five years after losing their employment. From a similar analysis using our simulated data, we find that, depending on the scale of the shock, displaced men have earnings losses of 9.4-11.1 percent and have 21.1-21.7 percent higher non-employment rates than their non-displaced counterparts.…”
Section: Employment Shocksmentioning
confidence: 88%
“…Previous literature has found large lasting negative effects of displacement on earnings (e.g., Jacobson et al, 1993;Davis and Von Wachter, 2011). Using a mass-layoff instrument, Bertheau et al (2023) found that displaced Swedish workers have a 5 percentage point higher probability of being unemployed and 10 percentage points lower earnings than non-displaced workers five years after losing their employment. From a similar analysis using our simulated data, we find that, depending on the scale of the shock, displaced men have earnings losses of 9.4-11.1 percent and have 21.1-21.7 percent higher non-employment rates than their non-displaced counterparts.…”
Section: Employment Shocksmentioning
confidence: 88%
“…ing workers displaced by the same firm, connected workers end up in a firm that pays, on average, higher wages. 25 Taking the ratio of this effect (0.0177) to the effect of the coworker link on entry-level wages without accounting for hiring firm characteristics (0.0417), one can learn how much of the wage effect comes from workers moving to firms with higher wage premia (e.g., Bertheau et al, 2023;Lachowska et al, 2020). The result of this exercise suggests that 40% of wage gain that connected workers obtain comes from moving to better-paying firms, while the remaining is likely to be associated with the better screening by firms when hiring connected candidates.…”
Section: The Value Of a Former Coworker In The New Firmmentioning
confidence: 99%
“…Moreover, given the larger relative effect, our findings suggest that coworker networks might be key to reducing the cost of job loss in those countries where such losses are larger. This is especially true because they not only reduce the incidence of (long-term) unemployment but also because they help avoid a critical source of post-displacement income losses: moving to worse firms and poorer workfirm matches (Bertheau et al, 2023;Raposo et al, 2021). Thus, from a policy perspective, one promising way to address the incidence of unemployment and alleviate the cost of job displacement is to encourage well-connected workers to rely on their networks in the job search process, while devoting the bulk of employment office resources to helping the not-so-well-connected.…”
Section: Conc Lusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant closure causes moderate but persistent shocks to parental labor market outcomes and family income. Exploiting the panel of job spells, we estimate event studies around plant closure akin to the standard approach in the broad literature on job loss e ects (e.g., Bertheau et al, 2022). In the years following plant closure, displaced parents exhibit an eight percentage point (p.p.)…”
Section: Introductionmentioning
confidence: 99%